LLC resonant charger with variable inductor control - Costa, Válter de Sousa (2016)
The present work pretends to study the operation and behavior of the LLC resonant converter topology considering a battery charging application, using the traditional switching frequency control and a new control variable, the variable inductance, provided by a current controlled device, the Variable Inductor (VI). During this work, a brief state of the art regarding general types of power converters and resonant power converters is presented. The LLC resonant converter topology and its advantages and disadvantages are described. The VI principle of operation and structure is presented and discussed and, in the end some information about batteries and its behavior under charging and discharging conditions is presented. The considered batteries characteristics for the studied battery charger are shown and the adopted charging profile is presented. In the following chapters, a theoretical analysis of the LLC resonant converter operation and behavior under switching frequency or VI control is performed and presented. A design methodology is proposed for the converter considering both switching frequency and VI control, separately or simultaneously. Simulations of the converter operation under open-loop condition were made, and simulation results were obtained and discussed. A prototype was built and test results were obtained. The prototype uses a SiC MOSFET (Silicon Carbide Metal Oxide-Semiconductor Field Effect Transistor) based inverter working at 100 kHz controlled with fiber optic drivers. To build the prototype, Printed Circuit Boards (PCB) were designed, manufactured and built. An high-frequency transformer and a VI were also design and built. Finally, theoretical, simulation and experimental results are confronted in order to reach conclusions regarding to the proposed design methodology and the prototype operation. This final analysis allows validating the LLC-VI resonant converter as a good option for a battery charger.